Exploring digital discourse: social network analysis approach to toxicity and interaction patterns - Singgalen, Yerik Afrianto (Institute of Computer Science (IOCS), 2024)
This study employs Social Network Analysis (SNA) to investigate the structural characteristics, dynamics, and toxicity levels within a digital discourse ecosystem. Using a dataset comprising threaded discussions and chain networks, we analyze the interactions among users and quantify the presence of harmful language. The SNA reveals a network comprising 453 nodes and 330 edges, highlighting the intricate web of connections among users. Additionally, toxicity analysis uncovers nuanced patterns of toxicity, with scores ranging from 0.01129 to 0.05852 across different categories. Further examination of network metrics such as Density, Reciprocity, Centralization, and Modularity provides insights into the network's organization and communication dynamics. Our findings offer valuable insights for content moderation, community management, and promotional strategies in fostering a safer and more inclusive online environment. This research contributes to advancing knowledge in digital communication and provides a foundation for future studies exploring challenges within online communities